2013
DOI: 10.1038/mt.2013.78
|View full text |Cite
|
Sign up to set email alerts
|

Recovery From Experimental Parkinsonism by Semaphorin-guided Axonal Growth of Grafted Dopamine Neurons

Abstract: Cell therapy in animal models of Parkinson's disease (PD) is effective after intrastriatal grafting of dopamine (DA) neurons, whereas intranigral transplantation of dopaminergic cells does not cause consistent behavioral recovery. One strategy to promote axonal growth of dopaminergic neurons from the substantia nigra (SN) to the striatum is degradation of inhibitory components such as chondroitin sulphate proteoglycans (CSPG). An alternative is the guidance of DA axons by chemotropic agents. Semaphorins 3A and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 50 publications
3
20
0
Order By: Relevance
“…Neural stem cells (NSCs) are self‐renewing with multipotency cells and can differentiate into various neural cells, such as astrocytes, oligodendrocytes, and neurons including dopaminergic neurons . Transplantation of dopaminergic cells derived from embryonic stem cells in a rat model of PD has shown that the grafted cells can survive, differentiate, and extend the processes beyond the graft core and establish synaptic contacts with the host striatum . Therefore, NSCs are considered as one of the most promising donor cells for the treatment of PD and other neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Neural stem cells (NSCs) are self‐renewing with multipotency cells and can differentiate into various neural cells, such as astrocytes, oligodendrocytes, and neurons including dopaminergic neurons . Transplantation of dopaminergic cells derived from embryonic stem cells in a rat model of PD has shown that the grafted cells can survive, differentiate, and extend the processes beyond the graft core and establish synaptic contacts with the host striatum . Therefore, NSCs are considered as one of the most promising donor cells for the treatment of PD and other neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This could facilitate the development of combination methods involving secreted guidance cues as used recently to elicit axon growth of intranigrally grafted esDA neurons in rats (Diaz-Martinez et al, 2013) along with substrate-anchored proteins to achieve efficient nigrostriatal DA axon growth in Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects underwent two 11 C‐DTBZ PET scans (test‐retest) separated by a 2‐month period [12 weeks (test), 20 ± 2 weeks (re‐test)], which is a typical age and period for the evaluation and follow‐up in animal models of PD after experimental treatments (Díaz et al, ; Díaz‐Martínez et al, ; Rodríguez‐Gómez et al, ). A Focus 120 PET scanner (CTI‐Concorde Microsystems LLC, Knoxville, TN) was used for PET data acquisition.…”
Section: Methodsmentioning
confidence: 99%